BERPIKIR DALAM PERSPEKTIF ALQURAN - Malkan Malkan (Hunafa: Jurnal Studia Islamika, 2007)
This article deals with التفكر in the Qur’an employing the thematic method of qur’anic exegesis. Observing the verses used the Qur’an, the writer found some words in the Qur’an denoting both negative and positive thinking. To denote the negative thinking, the word تتفكرون is used; to denote the things related to the prohibition of drinking liquor and of gambling; the word تعقلون is used; to denote the order to do good things; the word نظر is used; to denote al-Walid al-Mughirah’s negation to the Qur’an; to denote the unbelievers’ accuses of the prophet Muhammad, the word احلام is used. In the mean time, to denote the positive thinking, the Qur’an adopts the word يتفكرون  that is something related to the creature of the universe and of the natural phenomena; the word ينظر is used to denote the origin of human beings; the word اولو الالباب is used to denote agreement and negation to truth of the Qur’an. Kata Kunci: tafsir, berpikir, Alquran